Peran Motivasi Dalam Hubungan Kompetensi, Kepemimpinan Dan Pelatihan Terhadap Kinerja Pegawai Kementerian Agama Sumba Barat Daya - Lidwina Irma I Hondo; Paskalis Seran (Jurnal Kajian Ilmiah, 2025)
This article aimed to examine the influence of leadership, competence, and training on employee performance with motivation as a mediating variable at the Office of the Ministry of Religious Affairs in Southwest Sumba Regency. The study employed a literature review approach by analyzing various relevant scholarly sources published between 2015 and 2025. The findings revealed that leadership, competence, and training had a positive and significant impact on employee performance, both directly and through work motivation. Effective leadership encouraged employee morale and loyalty. Adequate competence improved confidence and work efficiency, while relevant training strengthened technical abilities and work attitudes. Motivation was proven to be a key factor mediating the influence of those three variables on improving employee performance. These findings emphasized that enhancing the performance of civil servants in the public sector requires strategic and integrated human resource management, particularly through improving work motivation.